(Table 1) Whole rock sulfur contents in basalts from DSDP Hole 53-418A - Ellen Gitlin (PANGAEA, 1985)
The behavior of sulfide minerals during the physical and chemical changes accompanying seafloor alteration was studied in three basalt flows from the bottom of DSDP Hole 418A, Leg 53. The rocks are mildly altered, and contain primary, authigenic, and vein sulfide minerals. Sulfide habit, mineralogy, and trace element content are inter-related and are correlated with the extent and type of silicate and oxide alteration. Incipient alteration at >90°-100°C was accompanied by low temperature reequilibration of pyrrhotite, and locally, by the oxidation of pyrrhotite to pyrite plus magnetite. The dominant stage of alteration, at </=90°C, is characterized by dissolution and local redistribution of pyrite and chalcopyrite, whose precipitation appears to be controlled by the water/rock ratio and the extent to which the water has been modified by reaction with the basalt. Chalcopyrite was concentrated relative to pyrite by slight changes in fluid composition caused by reaction with other minerals. Concurrent precipitation of smectite causes a net increase in rock volume, tending to restrict seawater access. Calculations of rock cooling rate through time suggest that the most prolonged hydrothermal circulation occurs at low temperatures, giving rise to pervasive low temperature alteration assemblages.
Supplement to: Gitlin, E (1985): Sulfide remobilitzation during low temperature alteration of seafloor basalt. Geochimica et Cosmochimica Acta, 49(7), 1567-1579, https://doi.org/10.1016/0016-7037(85)90262-5